1997
DOI: 10.1111/j.1469-0691.1997.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of distinct species of Borrelia burgdorferi sensu lato with neuroborreliosis in Switzerland

Abstract: OBJECTIVE: To evaluate by species-specific immunoblots the association of Borrelia burgdorferi sensu stricto, B. garinii and B. afzelii with neuroborreliosis in Switzerland. METHODS: Borrelia strains isolated from the cerebrospinal fluid (CSF) of three children with neuroborreliosis were typed by phenotypic and genotypic analysis. The serologic reactions (IgG) of these three patients as well as those of 28 patients, including one of these three children, with confirmed neuroborreliosis were characterized and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…The PCR-RLBA method was therefore used to analyze 18 cases of neuroborreliosis. The results showed that most patients had been infected with B. garinii (13 out of 18 patients [ Table 4]), in agreement with previous observations showing the preferential association of this genospecies with neurological complications (8,30,27). Moreover, the PCR-RLBA analysis revealed several cases of multiple infection (Table 1).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The PCR-RLBA method was therefore used to analyze 18 cases of neuroborreliosis. The results showed that most patients had been infected with B. garinii (13 out of 18 patients [ Table 4]), in agreement with previous observations showing the preferential association of this genospecies with neurological complications (8,30,27). Moreover, the PCR-RLBA analysis revealed several cases of multiple infection (Table 1).…”
Section: Discussionsupporting
confidence: 79%
“…To date only B. burgdorferi sensu stricto, B. garinii, and B. afzelii are known to be responsible for causing human disease (2,7,27,30). In fact, it seems that infections with B. burgdorferi sensu stricto tend to lead to arthritic symptoms, while those with B. garinii appear to cause neurological complications.…”
mentioning
confidence: 99%
“…neuroborreliosis are more frequently infected with B. garinii (8) or present serological reactions in accordance with this association (1,2,24,29). We have previously reported serological evidence for a pathogenic potential of B. valaisiana in humans (29).…”
mentioning
confidence: 68%
“…For example, different reservoir hosts were described for some Borrelia species (13)(14)(15). Similarly, several reports have suggested an association of particular clinical symptoms in human with some Borrelia species (1,2,10,24,29). The typing of B. burgdorferi sensu lato isolates is essential to clarify this specific point and consequently to understand the physiopathology of each Borrelia species (12,17,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation